2020
DOI: 10.3389/fcimb.2020.575656
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Health-Associated Oral Bacteria for Anticancer Properties in vitro

Abstract: While extensive literature exists about the role of oral bacterial pathogens like Porphyromonas gingivalis and Fusobacterium nucleatum in oral squamous cell carcinoma (OSCC), the role of health-associated species has been largely unexplored. In this study, we assessed the effect of Streptococcus mitis, Rothia mucilaginosa, Neisseria flavescens, Haemophilus parainfluenzae, Lautropia mirabilis , and Veillonella parvula on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 50 publications
(69 reference statements)
3
26
0
Order By: Relevance
“… 32 In OSCC cell lines, Lautropia mirabilis upregulated IL-6 and TNF-α, which are cytokines related to the inflammatory response. 42 All these genera were verified in LEfSe analysis in the current study.…”
Section: Discussionsupporting
confidence: 66%
“… 32 In OSCC cell lines, Lautropia mirabilis upregulated IL-6 and TNF-α, which are cytokines related to the inflammatory response. 42 All these genera were verified in LEfSe analysis in the current study.…”
Section: Discussionsupporting
confidence: 66%
“…It could be inferred that higher R.Mucilaginosa was always presented in cancer patients. What is more, it is reported R.Mucilaginosa upregulated TNF-α and upregulation of CD36 in all cell lines in cocultures [20] and increased abundance of R.Mucilaginosa exhibited the ability to produce acetaldehyde [21,22]. The above functional could explain the ndings of the present study that higher R.Mucilaginosa in esophageal cancerous tissue than that in para-cancerous.…”
Section: Discussionsupporting
confidence: 59%
“…Mechanisms of association of selected aerobic and anaerobic bacteria with tumors of the oral cavity are presented in Table 1 [ 4 , 9 , 15 , 16 , 17 , 18 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]; an overview of selected bacteria most frequently identified in association with OSCC is provided in Table S1 (Supplementary Materials) [ 12 , 13 , 14 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Oral Bacteria Associated With Oral Cancermentioning
confidence: 99%
“…Thus, it has been proposed as a possible early tumor marker [ 18 ]. On the other hand, Baraniya et al demonstrated the in vitro ability of S. mitis to inhibit OSCC tumor cell proliferation through cytotoxicity mediated by hydrogen peroxide production [ 37 ]. Nevertheless, although such a potential protective action could be attributed to S. mitis , these bacteria are also one of the major producers of carcinogenic acetaldehyde and, moreover, can induce the production of proinflammatory cytokines [ 76 ].…”
Section: Oral Bacteria Associated With Oral Cancermentioning
confidence: 99%